G-Protein-Coupled Receptors in CNS: A Potential Therapeutic Target for Intervention in Neurodegenerative Disorders and Associated Cognitive Deficits - Azam, Shofiul (Cells, 2020)
Neurodegenerative diseases are a large group of neurological disorders with diverse etiological and pathological phenomena. However, current therapeutics rely mostly on symptomatic relief while failing to target the underlying disease pathobiology. G-protein-coupled receptors (GPCRs) are one of the most frequently targeted receptors for developing novel therapeutics for central nervous system (CNS) disorders. Many currently available antipsychotic therapeutics also act as either antagonists or agonists of different GPCRs. Therefore, GPCR-based drug development is spreading widely to regulate neurodegeneration and associated cognitive deficits through the modulation of canonical and noncanonical signals. Here, GPCRs’ role in the pathophysiology of different neurodegenerative disease progressions and cognitive deficits has been highlighted, and an emphasis has been placed on the current pharmacological developments with GPCRs to provide an insight into a potential therapeutic target in the treatment of neurodegeneration.